NOS MARES DAS TRADUÇÕES, NOS MARES DAS TRAIÇÕES: Leminski, os diálogos com a cultura estrangeira e questões de poética e identidade - do Prado, Márcio Roberto (Review of International American Studies, 2016)
[For English, scroll to the bottom of the page] Márcio Roberto do Prado Universidade Estadual de Maringá-UEM Maringá Paraná Brasil "NOS MARES DAS TRADUÇÕES, NOS MARES DAS TRAIÇÕES: Leminski, os diálogos com a cultura estrangeira e questões de poética e identidade" Quando pensamos em Paulo Leminski (1944–1989), um dos aspectos que se destacam é sua relação com línguas e culturas estrangeiras, seja por meio de traduções especificamente concebidas e praticadas no âmbito literário, seja por conta de um diálogo cultural mais amplo que determinou rumos e possibilidades em sua produção artística e que contribuiu para o estabelecimento de uma persona literária que se confundia perigosa e provocativamente com o homem empírico. Deste modo, o presente artigo pretende, por meio de uma visão panorâmica de algumas de suas obras e de seu diálogo com a Poesia Concreta brasileira, tecer algumas considerações a respeito das propostas e das consequências desse projeto de Leminski, percebido ao longo de sua carreira. Ao fim, o que se verá é a (re)afirmação de uma obra viva que, por meio de traduções e traições de e para o Outro, ajuda-nos a compre ender a natureza e a herança da literatura brasileira na segunda metade do século XX (especialmente no caso da lírica), com consequências e lições que continuam válidas para os dias de hoje. Palavras-chave: Leminski; poesia concreta; tradução; cultura brasileira. "In the seas of translations, in the seas of betrayals: Leminski, the dialogues with a foreign culture and questions about poetics and identity" When we think of Paulo Leminiski (1944–1989) and of his artistic ‘signature’, it is his peculiar relation with the foreign languages and cultures that comes to the fore as one of the most important aspects of his work: an aspect determining his uniqueness. It manifests itself in his originally conceived translations and in his literary work in general—and, arguably, is traceable back to the wide cultural dialogue, to which Leminski was profoundly committed. His participation in that dialogue would both determine the directions of his development and open new possibilities affecting his artistic production, thus contributing to the establishment of his literary persona that would often, dangerously and provocatively, be confused with his empirical self. This paper aims to offer a panoramic view of some of Leminski’s works in the context of his dialogue with Brazilian Concrete Poetry in order to shed some light upon his lifelong projec in terms of his intellectual propositions and their consequences, or, less specifically, his expressive experiences collected throughout his career. In conclusion, the argument underlying this article leads to the (re)affirmation of Leminski’s living art, that, through translations/betrayals of the Other and for the Other, grants one an insight into the nature of Brazilian literature (and especially Brazilian lyrical poetry) of the first half of the 20th century. Leminski’s work provides his reader with an ideal point of departure to understand the cultural legacy of Brazil, whose turbulent history offers lessons that never lose validity. Keywords: Concrete poetry; translation; Brazilian culture, Paulo Leminski